Mucinous cystic neoplasm of the liver with biliary communication: an exception to the current classification - Anand, Santhosh (BMJ Case Rep, 2019)
Cystic neoplasms of the liver are rare tumours. According to the recent WHO classification, they are classified into mucinous cystic neoplasm and intraductal papillary neoplasm based on the presence of ovarian-like stroma and biliary communication. We report two rare cases of mucinous cystadenoma of the liver with biliary communication and discuss the shortcomings of current classification.